Neuromuscular Compensation Mechanisms in Vocal Fold Paralysis and Paresis - Dewan, Karuna (Laryngoscope, 2017)
INTRODUCTION: Vocal fold paresis and paralysis are common conditions. Treatment options include augmentation laryngoplasty and voice therapy. The optimal management for this condition is unclear. The objective of this study was to assess possible neuromuscular compensation mechanisms that could potentially be used in the treatment of vocal fold paresis and paralysis. METHODS: In an in vivo canine model we examined three conditions: (1) unilateral right recurrent laryngeal nerve (RLN) paresis and paralysis, (2) unilateral superior laryngeal nerve paralysis (SLN), and (3) unilateral vagal nerve paresis and paralysis. Phonatory acoustics and aerodynamics were measured in each of these conditions. Effective compensation was defined as improved acoustic and aerodynamic profile. RESULTS: The most effective compensation for all conditions was increasing RLN activation and decreasing glottal gap. Increasing RLN activation increased the percentage of possible phonatory conditions that achieved phonation onset. SLN activation generally led to decreased number of total phonation onset conditions within each category. Differential effects of SLN (CT muscle) activation were seen: Ipsilateral SLN activation could compensate for RLN paralysis, normal CT compensated well in unilateral SLN paralysis, and in vagal paresis/paralysis contralateral SLN and RLN display antagonistic relationships. CONCLUSIONS: Methods to improve glottal closure should be the primary treatment for large glottal gaps. Neuromuscular compensation is possible for paresis. This study provides insights into possible compensatory mechanisms in vocal fold paresis and paralysis.